TheraDrive: a new stroke therapy concept for home-based, computer-assisted motivating rehabilitation - Johnson, M.J.; Trickey, M.; Brauer, E.; Feng, X. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2004)
Stroke results in functional arm impairments that persist even after rehabilitation training. The increasing numbers of persons at-risk in the population for stroke creates an increased need for therapy programs that can be effectively administered in both home and outpatient clinics. The aim of this work is to create a low-cost, commercially-viable, home-based rehabilitation system that can capitalize on computer-assisted motivating rehabilitation concepts of game therapy and skill training with functional training related to real activities to induce user-dependent CNS plasticity. The TheraDrive concept combines the motivational elements of relearning steering tasks with playing driving video games using commercial force-feedback steering wheels to create an upper arm stroke therapy environment that is usable at home or in the clinic. This paper presents the concept and reports on investigations to evaluate the main commercial building blocks for the prototype: the steering wheel and driving software. Evaluation results of three force-feedback steering wheels and the driving gaming software called SmartDriver are presented. Future evaluation trials with stroke subjects will be completed.